Dating preferences and experiences of UPV College students. - Garcia, Yuba Mia
The study aims to determine the dating preferences and experiences of UPV college students. Fifty students from the Division of Social Sciences between the ages of 17 and 19 years old are the respondent in this study. They were chosen through fish ball sampling. Data collection was done using the questionnaire. Data were analyzed using simple frequency and percentages. The results of the study reveal that for both male and female, physical attractiveness significantly matters in selecting a dating partner. Male respondents prefer to date someone who is a good conversationalist while females prefer to date somebody who has a good sense of humor. In dating, status of dates is of least consideration by both male and female., Results of the study further show that most of the dates of the respondents are people they met in school through friends. Malls and movie houses are places where the respondents usually have their dates. common dating activities include eating, having a conversation and hanging around. Results also show that it is the male who usually initiate the date and paid for the dating expenses. But there are females who also make the first move and also paid for the dating expenses. As a recommendation, the researchers suggest that some factors can be considered in the research such as the social status and religion. In addition, the researchers also recommend to conduct studies with different sets of respondents like young professionals from various organizations as well as non-professionals